On the Solubility of Benzoic Acid in Aqueous Carboxymethylcellulose Solutions - Kumar S.; Upadhyay S.N.; Mathur V.K. (My University, 2025)
Solubility of benzoic acid in distilled and demlnerallzed water and aqueous CMC solutions containing 0.5, 1.0, 1.5, and 2.0% polymer by weight has been determined in the temperature range of 15-45 °C. At any given temperature, the solubility In the polymer solution Increases with polymer concentration and seems to approach a constant value at higher concentrations. © 1978, American Chemical Society. All rights reserved.